P328 Crohn's colitis care (CCCare): development and testing of a bespoke cloud-based clinical management system for inflammatory bowel disease (IBD). (16th January 2018) - Krishnaprasad, K; Walsh, A; Begun, J; Bell, S; Carter, D; Grafton, R; Sechi, A; Sewell, K; McMahon, A; Connor, S; Radford-Smith, G; Andrews, J; et al.
Abstract: Background: A recent Australian audit of IBD care identified variation in care and poor documentation as major problems. To address these, the Australia and New Zealand Inflammatory Bowel Disease Consortium (ANZIBDC) worked to develop a comprehensive cloud based IBD clinical management system—"Crohn's Colitis Care" (CCCare). The ANZIBDC is made up of 14 centres across Australia and New Zealand, providing care for 20000 patients with IBD. Methods: The ANZIBDC sent out a request for proposal and worked with the selected software developer. The development team included gastroenterologists, IBD nurses, and IT specialists. Clinical guidelines, standards of care, and usual practice across the 14 sites informed development. CCCare thus captures symptoms, imaging, endoscopy, blood results, medications in standardised fields along with clinic letters, and other correspondence in a single IBD-specific medical record. Safety monitoring, disease management plans, patient reminders, patient portal, and summary reports are all available. De-identified longitudinal data are stored separately in a clinical quality registry. CCCare was tested for feasibility and usability, in two large ANZIBDC sites—the Royal Adelaide and Royal Brisbane Hospitals. Testing assessed use in day-to-day clinical settings including face-to-face, telehealth, and virtual clinic encounters. The patient portal, wherein they enter their history and patient reported outcomes, was also tested. Users' reactions to CCCare were evaluated with the system usability scale (SUS). SUS broadly classifies usability of a system from poor (<70) to superior (>90). Standardised qualitative feedback was also captured through face to face or telephone interview. System security was assessed by commercial penetration testing. Results: Results from 13 users [clinicians ( n = 3), nurses, administrative staff and patients] showed a mean SUS score of 75 (50 – 95). The "Usability" and "Learnability" sub-scores were 77 and 68, respectively. All user groups rated the software as user-friendly and intuitive qualitatively. Patients anticipated better communication with clinical team and improved ability to track their own disease. Clinicians identified structured recording of adherence, the standard management plan to support best practice and centralised data repository as positive features. Penetration test was passed successfully which assured that CCCare is suitable for deployment into the health sector. Conclusions: Preliminary feedback demonstrates that CCCare is usable an secure, and is now ready for use in routine clinical care. We anticipate that using CCCare will create enormous opportunity for improvements in clinical care and uniform data collection.